A butterfly shaped organic heterojunction photocatalyst for effective photocatalytic CO2 reduction. Issue 28 (2nd July 2021) - Hayat, Asif; Sohail, Muhammad; Taha, T. A.; Alenad, Asma M.; Irfan, Ahmad; Shaishta, Naghma; Hayat, Ashiq; Mane, Sunil Kumar Baburao; Khan, Wasim Ullah
Abstract : The modification of carbon nitride (CN) for visible light photocatalytic CO2 reduction is an important issue to explore in the context of energy and environmental challenges. Abstract : The modification of carbon nitride (CN) for visible light photocatalytic CO2 reduction is an important issue to explore in the context of energy and environmental challenges. The current work describes the fabrication of a butterfly-shaped photocatalyst derived from a heterojunction between the electron-rich organic monomer 2, 5-dibromothiophene (TP) and a CN framework via copolymerization (UCN-TP). The successful incorporation of TP within CN means that it acts as a nucleophilic spare entity that provides electron solidity (π-conjugation) via charge allocation and increases the photocatalytic activity of CN (under visible light illumination). Density functional theory (DFT) data provide additional information on the amalgamation of TP inside CN and the reduced band gap. The best sample UCN-TP0.06 generated 68.18 μmole of CO and 18.52 μmole of H2 by photoreduction, demonstrating the highest photocatalytic activity. Moreover, this remarkable modification of the chemical configuration, band gap and surface area encouraged the good detachment of light-produced photons, thereby rendering it the best candidate for the photoreduction of CO2 .